PEMAHAMAN á¸¤ADITH (Definisi, Aliran, dan Afilisasi) - Hariono, Duwi (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
The terms in hadith study is often ambiguous and difficult to differentiate. As the terms of hadith, sunah, khabar, and atsar are often used at the same time. For hadith observers, it becomes serious problem and complicated since those terms have significant difference. Hence, the same usage of those terms cannot be accepted. One of the debatable issues in discussing hadith study is about disagreement in defining the term of hadith understanding. The hadith scholars mention it in three terms: fiqh al-á¸¥adith, fahm al-á¸¥adith dan naqd al-á¸¥adith. Each term has different perception related to its scope and limitation. One should be underlined that although those terms are different, the purposes are same namely hadith understanding activities. This article discusses the definition of fiqh al-á¸¥adith, fahm al-á¸¥adith dan naqd al-á¸¥adith and their sects and affiliation of hadith understanding. Keywords: Fiqh al-á¸¥adith, fahm al-á¸¥adith, naqd al-á¸¥adith, sects, affiliation